2022
DOI: 10.1093/mnras/stac3472
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the galaxy UV luminosity function at redshifts z ≃ 8 – 15 from deep JWST and ground-based near-infrared imaging

Abstract: We reduce and analyse the available James Webb Space Telescope (JWST) ERO and ERS NIRCam imaging (SMACS0723, GLASS, CEERS) in combination with the latest deep ground-based near-infrared imaging in the COSMOS field (provided by UltraVISTA DR5) to produce a new measurement of the evolving galaxy UV luminosity function (LF) over the redshift range z = 8 − 15. This yields a new estimate of the evolution of UV luminosity density (ρUV), and hence cosmic star-formation rate density (ρSFR) out to within <300 My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
215
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(235 citation statements)
references
References 61 publications
15
215
5
Order By: Relevance
“…The dropout nature of this source satisfies some of the color criteria to identify z > 10 galaxy candidates. Indeed, it satisfies the criterion of m 150W − m 200W > 0.8 used in Yan et al (2023), and some (but not all) of the criteria used in Donnan et al (2023), with a 2σ nondetection in F115W and F150W, and >3σ detections in redder filters (see Figure 2 and Table 1). However, the identification of this source as a DSFG calls into question such a very high-redshift scenario, given that the highest-redshift dust continuum detections ever reported are at z ∼ 7-8 (Laporte et al 2017;Strandet et al 2017;Marrone et al 2018;Tamura et al 2019;Inami et al 2022).…”
Section: A Jwst/nircam Dropout: a Dsfg At Redshift Fivementioning
confidence: 83%
See 2 more Smart Citations
“…The dropout nature of this source satisfies some of the color criteria to identify z > 10 galaxy candidates. Indeed, it satisfies the criterion of m 150W − m 200W > 0.8 used in Yan et al (2023), and some (but not all) of the criteria used in Donnan et al (2023), with a 2σ nondetection in F115W and F150W, and >3σ detections in redder filters (see Figure 2 and Table 1). However, the identification of this source as a DSFG calls into question such a very high-redshift scenario, given that the highest-redshift dust continuum detections ever reported are at z ∼ 7-8 (Laporte et al 2017;Strandet et al 2017;Marrone et al 2018;Tamura et al 2019;Inami et al 2022).…”
Section: A Jwst/nircam Dropout: a Dsfg At Redshift Fivementioning
confidence: 83%
“…The SCUBA-2 observations from Zavala et al (2017) partially overlap with the CEERS NIRCam survey and thus can be used to look for dust continuum emission around z > 10 candidates in the field. Here we focus on two recently reported high-redshift candidates: CEERS-93316 reported to be at z ≈ 16.7 (Donnan et al 2023) and Maisie's galaxy at z ≈ 11.8 (Finkelstein et al 2022a).…”
Section: Searching For Dsfg Contaminants In High-redshift Lbgmentioning
confidence: 99%
See 1 more Smart Citation
“…The 6.5 m space observatory is expected to be a game changer in the field of extragalactic observations. Numerous papers have claimed the first detection of ultra high-redshift galaxies at z  10, waiting for spectroscopic confirmation (e.g., Adams et al 2023;Castellano et al 2022;Donnan et al 2023;Finkelstein et al 2022aFinkelstein et al , 2022bHarikane et al 2022b;Naidu et al 2022). Likewise, the superb sensitivity of JWST may also enable us to witness rapidly accreting seed BHs far beyond the current samples of high-redshift AGNs.…”
Section: Introductionmentioning
confidence: 99%
“…Among the candidates reported by Castellano et al (2022), there is also a very bright object at z ph = 12.3 in GLASS with F444W magnitude of 25.88. In CEERS, Donnan et al (2023) found a candidate at z ph = 16.74 that has an F200W magnitude of 26.46. All such objects, if at the high redshifts suggested, would correspond to M UV  −21.5 to −24, a regime where no previous studies had suggested finding any galaxies over such a small area as a few NIRCam pointings.…”
Section: Introductionmentioning
confidence: 99%